INIA 333-CHUGAYNA new Potato Variety Resilient to Climate Change for the Family Farming System with Tolerance to Frost, Resistant to Late Blight and high Quality for Fresh Consumption - Cabrera, H.; Otiniano, R.; Pando, R.; Garcia, H.S.; Rodriguez, W.H.; Pérez, J.M.; Haan, Stef de; Gastelo, M. (2025)
The new potato variety INIA 333-CHUGAYNA, is the result of the joint work of the NGO Asociaci & oacute;n Pataz, INIA and the International Potato Center, it was generated through traditional breeding and the use of the participatory varietal selection methodology, as a variety resilient to climate change with frost tolerance, resistance to late blight, compared to the improved variety INIA 302-Amarilis and the native varieties, Huevo de Indio. This new variety is also resilient to climate change, tolerant to frost, with field resistance to late blight, high tuber yield, low glycoalkaloid content and high quality for fresh consumption, adapted up to 4000 m above sea level. It was released in 2023 and officially registered in the national registry of commercial varieties of Peru. The new variety INIA 333-CHUGAYNA requires minimal use of fungicides and has a high economic profitability that will improve the living standards of small and medium-sized farmers in Peru. It can also be used as a parent in breeding programs in other countries in development, to confront climate change, especially frost.